Peningkatan Nilai CBR Tanah Dasar (Sub Grade) dengan Penambahan Kapur dan Abu Sekam Padi - Liliwarti - - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2019)
The subgrade is very important on road construction, because its functions for support the traffic loads. The subgrade is not able to bearing capacity the traffic load , can cause damage such as cracks, settlement,and deformation on the flexible pavement or rigid pavement. to solve in this problems, it is necessary to improve the mechanical properties of subgrade for increasing soil bearing capacity and reducing the swelling potential. The Sicincin ring road - Lubuk Alung, Padang Pariaman district which has deformed, settlement and cracks on the road pavement, caused by poor bearing capacity of the subgrade. To solve these problems, it is necessary to have the soil improvements (stabilization) for subgrade In this paper soil stabilization is done by mixing soil with lime and rice husk ash (variations in lime content of 5%, 8%, 11%, 14% and 17%) and rice husk ash (constant 2.5%) .The compaction test and CBR test is carried for each variation. The results in this study obtained the most optimal percentage of lime + rice husk ash is 11%, CBR design is 25%, and swelling value of 0.13%. CBR value of subgrade without lime and rice husk ash obtained CBR = 2.3%. So that there is a significantly increase in CBR value if using lime and rice husk ash as stabilization material for subgrade. These results can be used by experts to choose effective stabilization methods.